Can apical ballooning cardiomyopathy and anterior STEMI be differentiated based on β1 and β2-adrenergic receptors polymorphisms?. (15th November 2015) - Vriz, Olga; Minisini, Rosalba; Zito, Concetta; Boccato, Elisa; Fimiani, Fabio; Pirisi, Mario; Facciolo, Caterina; Limongelli, Giuseppe; Bossone, Eduardo; Calabrò, Paolo
Abstract: Aim: Catecholamine excess along with an exaggerated sympathetic stimulation appears to play a major role in the pathophysiological mechanism of tako-tsubo cardiomyopathy (TTC), which mimics acute ST-elevation myocardial infarction (STEMI). The aim of the present study was to investigate differences in the distribution of allelic variants of β1- and β2-adrenoceptors between TTC and anterior STEMI patients compared to normal subjects. Methods and results: β1- and/or β2-adrenoceptor polymorphisms in 97 patients with TTC (92 females, 96%; mean age 66.8 ± 11.6 years; range 35 to 87 years) were compared with 81 patients with anterior STEMI (77 females, 95%; mean age 72.5 ± 12.8 years; range 32 to 96 years) and 101 controls (95 females, 94%; mean age 62.3 ± 10.4 years; range 44 to 92 years). Differences in genotype frequencies were assessed using the Pearson χ 2 test. β1-Adrenoceptor (Gly389Arg) and β2-adrenoceptor (Arg16Gly and Gln27Glu) genotype frequencies were significantly different among groups (p < 0.001, p = 0.024, p = 0.008, respectively). However, differences did not achieve statistical significance when TTC and anterior STEMI patients were compared by post-hoc analysis. The cardiovascular risk factor profile was worse in anterior STEMI patients, who more often had a history of systemic arterial hypertension, diabetes and coronary artery disease. Conclusions: In a large TTC cohort compared with anterior STEMI patients, β-adrenoceptor polymorphisms were similar. However, the cardiovascular risk factor profile was different between the two groups. β-Adrenoceptor polymorphisms in TTC patients differed from normal subjects. Highlights: β-Adrenoceptor polymorphisms are similar in the two groups. Different cardiovascular risk factor profile among TTC and STEMI patients On top of sympathetic pathway, they are fundamental contributors in STEMI.